Deciphering a Nanocarbon‐Based Artificial Peroxidase: Chemical Identification of the Catalytically Active and Substrate‐Binding Sites on Graphene Quantum Dots1. (4th May 2015) - Sun, Hanjun; Zhao, Andong; Gao, Nan; Li, Kai; Ren, Jinsong; Qu, Xiaogang
Abstract The design and construction of efficient artificial enzymes is highly desirable. Recent studies have demonstrated that a series of carbon nanomaterials possess intrinsic peroxidase activity. Among them, graphene quantum dots (GQDs) have a high enzymatic activity. However, the catalytic mechanism remains unclear. Therefore, in this report, we chose to decipher their peroxidase activity. By selectively deactivating the ketonic carbonyl, carboxylic, or hydroxy groups and investigating the catalytic activities of these GQD derivatives, we obtained evidence that the CO groups were the catalytically active sites, whereas the OCO groups acted as substrate‐binding sites, and COH groups can inhibit the activity. These results were corroborated by theoretical studies. This work should not only enhance our understanding of nanocarbon‐based artificial enzymes, but also facilitate the design and construction of other types of target‐specific artificial enzymes.